Non-reproductive Risk Factors of Uterovaginal Prolapse- the Lesser Known Perils - Paudyal, Pooja; Pradhan, Neelam; Ojha, Neebha (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: The aim of this study was to analyze the non-reproductive risk factors associated with uterovaginal prolapse (UVP) which is a major health concern of women. Methods: This was a hospital-based case control study, carried out in the Gynaecology Department of Tribhuvan University Teaching Hospital (TUTH) over one year from 13th April 2011 to 12th April 2012). Cases comprised of 116 women with UVP, second degree or more and controls were women without prolapse of the same age group within five years admitted subsequently after the cases. The variables studied were medical disorders like chronic obstructive pulmonary disease (COPD)/chronic cough, constipation; smoking, family history of prolapse and body mass index (BMI). The p-value and odds ratio (OR) for each risk factor were calculated. Multivariate analysis was done for those risk factors found to be significant from the univariate analysis. Results: Smoking, family history of prolapse and low BMI were found to be significant risk factors from univariate analysis. Only two risk factors- family history of prolapse with OR 5.52 (2.11-14.49) and being underweight with OR 15.38 (1.88-125), were found to be significant by multivariate analysis. Conclusion: Providing good nutrition and preventing malnourishment in postmenopausal women, imparting awareness about increased risk in women with history of prolapse in first degree relatives and educating about the perils of smoking could contribute in reducing morbidity due to prolapse.